Frontispiece: Structural Mass Spectrometry of Membrane Proteins within Their Native Lipid Environments. Issue 51 (12th September 2018) - Reading, Eamonn
Abstract : The potential capability of structural mass spectrometry (MS) for deciphering membrane protein behavior within native environments has been highlighted. MS has become an important method for membrane protein structural biologists due to its ability to determine a broad range of protein structural information, such as stoichiometry, subunit connectivity, structural dynamics, solvent accessibility, complex formation, and ligand binding. For more information see the Concept article by E. Reading onpage 13391 ff.